2016
DOI: 10.17269/cjph.107.5230
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and the risk of female breast cancer among participants of the Canadian National Enhanced Cancer Surveillance System

Abstract: OBJECTIVES:The role of diet in the etiology of breast cancer is not well understood despite extensive research. In the majority of this work, a single nutrientbased approach has been used which does not take into account combinations of food that are consumed. An alternative to the single nutrient approach is to identify patterns in the dietary intake information and relate these patterns to disease incidence. This investigation characterized dietary patterns among participants of a Canadian case-control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns. Four studies exclusively used the a priori approach resulting in a total of 6 studies that used the a priori approach for the identification of dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns. Four studies exclusively used the a priori approach resulting in a total of 6 studies that used the a priori approach for the identification of dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, five were significantly associated with greater risk of breast cancer (46,47,50,54,56). Null findings were reported in five studies, with risk estimates favoring a slightly greater risk of unhealthy dietary patterns in three (52,55,57), and slightly lower risk in one study (50). One study showed no association between an unhealthy dietary pattern and breast cancer risk (50).…”
Section: Posteriori/exploratory Approach: Unhealthy Dietary Patternmentioning
confidence: 91%
See 1 more Smart Citation
“…The epidemiologic evidence for associations between dietary factors and breast cancer is weak and etiologic mechanisms are often unclear in spite of comprehensive research. [2930] It has been reported that utilization of meat is associated with heterocyclic amine exposure. [31] In this study, multivariate analysis did not show a significant correlation between dietary meat and IBC.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches have revealed that some of the dietary patterns are associated with the risks of cancer. So, the change in abnormal diet patterns might also help in prevention of progression of cancer (Van Ryswyk et al, 2016;Hirose et al, 2007). Furthermore, research databases from different nations have concluded that the incidence of cancer progression is low in persons eating sufficient amounts of antioxidants containing fruits or vegetables regularly (Liu, 2003;Shirzad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%